Socioeconomic diagnosis of small farmers in the Tracateua community, Municipality of Moju, Pará, Brazil (Research, Society and Development, 2021)
Family farming is fundamental for the sustainable economic development of rural areas (Lima & Wilkinson, 2002), having great importance in the absorption of labor, in the generation of jobs and in the local, territorial food, nutritional and productive production of peoples. rural and urban areas (Gomes, 2017). The works developed in the Brazilian agrarian communities are of fundamental importance for the country's economy, essentially, in the contemporary world, for small rural communities. Starting from this point, the objective of this work was to identify and evaluate the socioeconomic characteristics and the profile of farmers in the Tracateua community, located in the municipality of Moju (PA). The study was developed in the Tracateua community, municipality of Moju, State of Pará, which is located at the Embrapa branch, at km 30 of PA 150, located approximately 38 km from the municipality's headquarters (Moju) and 295 km from the city of Belém In the community of Tracateua, municipality of Moju, there is no reserve of labor to dedicate to family farming. The products most produced in the community are cassava, corn, beans, rice and passion fruit, with cassava being the main product, sold in the form of flour. As for the relationship between the studied variables, the correlation between them can be considered average. The main socioeconomic factors that stand out the most are: the relationship of time in the community with the family's monthly income, other incomes, size of the property, education of the head of the family and area of cultivation and the Age of the head of the family influences the number of children.